High Perceived Stress May Shorten Activated Partial Thromboplastin Time and Lead to Worse Clinical Outcomes in Patients With Coronary Heart Disease - Yin, Han; Cheng, Xingyu; Liang, Yanting; Liu, Anbang; Wang, Haochen; Liu, Fengyao; Guo, Lan; Ma, Huan; Geng, Qingshan (Frontiers in Cardiovascular Medicine, 2021)
Objective: To determine the association of perceived stress with coagulation function and their predictive values for clinical outcomes. Methods: This prospective cohort study derived from a cross-sectional study for investigating the psychological status of inpatients with suspicious coronary heart disease (CHD). 10-item Perceived Stress Scale (PSS-10) as an optional questionnaire was used to assess the severity of perceived stress. Coagulation function test including activated partial thromboplastin time (APTT), prothrombin time (PT), and fibrinogen were measured within 1 hour after admission. 241 CHD patients out of 705 consecutive inpatients were included in analyses and followed with a median of 26 months for clinical outcomes. Results: Patients in high perceived stress status (PSS-10 score >16) were with shorter activated partial thromboplastin time (APTT) (36.71s vs. 38.45s, p=0.009). Shortened APTT (≤35.0s) correlated with higher PSS-10 score (14.67 vs. 11.22, p=0.003). Association of APTT with depression or anxiety was not found. Multiple linear models adjusting for PT estimated that every single point increase in PSS-10 was relevant to approximately 0.13 second decrease in APTT (p=0.001) regardless of the type of CHD. APTT (every 5 seconds increase: HR 0.68 [0.47-0.99], p=0.041) and perceived stress (every 5 points increase: HR 1.31 [1.09-1.58], p=0.005) could predict cardiovascular outcomes. However, both predictive values would decrease when the they were simultaneously adjusted. After adjusting for physical clinical features, the associated of perceived stress on cardiac (HR 1.25 [1.04-1.51], p=0.020) and composite clinical outcomes (HR 1.24 [1.05-1.47], p=0.011) persisted. Conclusions: For patients with CHD, perceived stress strongly correlates with APTT. The activation of intrinsic coagulation pathway is one of the mechanisms that high perceived stress causes cardiovascular events. This hints an important role of the interaction of mental stress and coagulation function on cardiovascular prognosis. More attention needs to be paid to CHD patients with high perceived stress.